Eat All Through Radiation Therapy (EAT‐RT): Structured therapy model to facilitate continued oral intake through head and neck radiotherapy—User acceptance and content validation. Issue 9 (23rd May 2020) - Hutcheson, Katherine A.; Gomes, Andrea; Rodriguez, Veronica; Barringer, Denise; Khan, Maisha; Martino, Rosemary
Abstract: Background: To develop and examine user acceptance and content validity of a structured program to facilitate safe but challenging oral intake during radiotherapy (RT) delivered by a speech language pathologist (SLP)—the Eat‐All Through Radiation Therapy (EAT‐RT) program. Methods: EAT‐RT was developed through expert consensus of SLPs at the Princess Margaret Cancer Centre (Canada) and M D Anderson Cancer Center using a conceptual framework of a diet hierarchy and a mealtime routine. EAT‐RT was refined by practicing SLPs, and then disseminated for a 4‐week clinical pilot at seven sites who were subsequently invited to participate in an online survey. Results: Twelve SLPs from six sites piloted EAT‐RT therapy with a median of eight patients (IQR: 2‐15) before and/or during RT. All SLPs reported EAT‐RT added value to their practice, harmonized well with exercises, and its content was helpful; 11 (92%) reported EAT‐RT facilitated patient understanding and indicated the desire to continue using EAT‐RT. Conclusion: The EAT‐RT program was accepted by North American SLPs. The findings support the content and value of EAT‐RT to facilitate oral intake in patients with head and neck cancer throughout RT.